ITOIGAWA SHIMPAKU PROJECT: LINKING CULTURAL, NATURAL AND GEOLOGICAL HERITAGE FOR SUSTAINABLE TOURISM - Theodore Brown; Takeo Kobayashi (Badan Pelaksana Rinjani-geopark Rinjani Lombok, 2021)
Bonsai is a cultural tradition with roughly 1,300 years of history in Japan, recognized and appreciated across the world. One of the most prized subjects in bonsai is the Sargent juniper (Juniperus chinensis var. sargentii), called ‘shimpaku’ in Japanese. A particularly well-regarded variety of shimpaku was discovered in Itoigawa in the early 20th century. The ‘Itoigawa Shimpaku’ is prized for its tightly bunched leaves, beautiful white wood and exceptional hardiness. It thrives in the rugged mountains of Itoiga-wa which formed along the Itoigawa-Shizuoka Tectonic Line, a massive fault closely connected to the formation of the Japanese island arc. After decades of collection, the Itoigawa Shimpaku has largely disappeared from its native habitats. Aging local communities are unable to manage the tree’s native mountains and forests. Furthermore, younger generations are less interested in traditional arts making the future of the Itoigawa Shimpaku increasingly uncertain. In response to these issues, Itoigawa UNESCO Global Geopark launched the Itoigawa Shimpaku Project to engage local commu-nities in how best to preserve this unique local heritage and to share it with a wider audience through community-led, experience-oriented tourism programs which link geological, natural and cultural heritage. The aim of this project is to encourage sustainable development, raise new generations of bonsai practitioners and promote responsible management of forests and mountains to en-sure the Itoigawa Shimpaku’s future for centuries to come. This paper will discuss the history of the Itoigawa Shimpaku as well as the background, main issues, and the current progress and future plans of the Itoigawa Shimpaku Project.